EFFECTS OF METABOLIC SYNDROME ON PREGNANCY OUTCOMES; A COMPARATIVE STUDY - Smriti Bhargava, Sukh Chain, Rakesh Kumar Ola (South Eastern European Journal of Public Health, 2025)
KEYWORDS Metabolic syndrome, pregnancy outcomes, gestational diabetes, hypertensive disorders ABSTRACT: Background: Metabolic syndrome (MetS) is a cluster of metabolic abnormalities, including central obesity, insulin resistance, hypertension, and dyslipidemia, that significantly increase the risk of adverse pregnancy outcomes. Given the rising prevalence of MetS globally, its impact on maternal and fetal health has become a critical area of research. Objective: This study aims to evaluate the effects of MetS on pregnancy outcomes by conducting a prospective comparative observational study in the Department of Obstetrics and Gynecology at PDU Medical College, Churu, Rajasthan Methods: A total of 200 pregnant women were enrolled and divided into two groups: Group A (MetS, n=100) and Group B (Control, n=100). MetS was diagnosed based on the revised NCEP ATP III criteria. Maternal outcomes, including gestational diabetes mellitus (GDM), hypertensive disorders of pregnancy (HDP), preterm birth, mode of delivery, and postpartum complications, were assessed. Neonatal outcomes such as birth weight, Apgar scores, NICU admissions, and perinatal mortality were also evaluated. Data were analyzed using SPSS version 25.0, with statistical significance set at p< 0.05. Results: Women with MetS had significantly higher rates of GDM (40% vs. 12%, p< 0.001), HDP (35% vs. 10%, p< 0.001), preterm birth (22% vs. 8%, p = 0.005), and cesarean delivery (58% vs. 32%, p< 0.001) compared to controls. NICU admissions were significantly higher in neonates born to MetS mothers (25% vs. 7%, p< 0.001), and they also had a higher prevalence of low birth weight (28% vs. 10%, p = 0.002) and macrosomia (18% vs. 5%, p = 0.01). Multivariate logistic regression analysis identified MetS as an independent risk factor for adverse pregnancy outcomes. Conclusion:MetS in pregnancy is associated with an increased risk of GDM, HDP, preterm birth, cesarean delivery, and adverse neonatal outcomes. Early screening and targeted interventions for women with MetS may help improve maternal and fetal health outcomes.